Sonochemical-assisted biosynthesis of silver nanoparticles using cymbopogon nardus L. essential oil: advanced process optimization through response surface methodology - Guardiola Rosa Wira; Hijria Putri Maharani; Nove Kartika Erliyanti; Renova Panjaitan; Caecilia Pujiastuti (Konversi, 2025)
This research investigates the fabrication and characterization regarding silver nanoparticles (AgNPs) utilizing essential oil derived from citronella leaves (Cymbopogon nardus L.) as a bioreductant. The synthesis method employed is sonochemistry, with variations in pH levels to determine optimal conditions for AgNPs yield. The use of essential oil as a bioreductant offers eco-friendly advantages and high efficiency in reducing metal ions. The results indicate that the highest yield of 8.67% was achieved at pH 9.0280 and 59.7190 minutes of sonochemical processing. Statistical optimization of processing parameters was conducted to maximize the yield of AgNPs, with the optimization process analyzed using Response Surface Methodology (RSM). The sequence of experimental runs, condition variations, and obtained results were determined using the Central Composite Design (CCD). The model demonstrates a strong correlation with the experimental data, exhibiting an adjusted R² value of 0.9684. A high F-value of 30.61 and a low p-value of 0.0009 suggest that the regression model is statistically significant and effectively accounts for variations in AgNPs yield. The lack-of-fit value for the model is 0.0359, indicating no significant discrepancy between the experimental data and the model's predicted values. The successful formation of AgNPs was confirmed, with absorption peaks observed within the 400–450 nm range.